Private copying levies. Roszczenie od posiadaczy urządzeń reprograficznych z art. 20 ustawy o prawie autorskim i prawach pokrewnych oraz jego przedawnienie - Tylec, Grzegorz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents a general outline of the legal structure regarding levy system to compensate authors and publishers for ‘reproductions on paper or any similar medium, effected by the use of any kind of photographic technique or by some other process having similar effects. These regulations are included in art. 20 and 201 Polish Act on Copyright and Related Rights. In a special way, has been analyzed problem of claim due and limitation of claim levies from holders of reprographic devices who conduct business in the field of reproduction of works for their own personal use, described in art. 201 Polish Act on Copyright and Related Rights.